Empowering Financial Literacy: Unleashing The Potential of Indonesian Fishermen: Empowering Indonesian Fishermen’s Financial Literacy - Putri, Rizky Dwi; Huang, Wen-Chi (Journal of Tropical Rural Development, 2025)
Background and purpose – Financial literacy represents a critical component of economic resilience, yet research on its determinants among fishing communities remains limited. This study investigates the multifaced factors influencing financial literacy among fishermen in Indonesia, employing a comprehensive analytical approach that examines socioeconomic, demographic, and digitalization. Methodology – This study utilizes the Tobit model to investigate how factors such as education level, age, professional experience, geographical location, and internet use interact to influence financial knowledge and skills. Findings – The findings indicate that years of formal education are no longer the only one key determinant of financial literacy. Instead, factors related to education like numeracy, internet use, and the possible of informal education proxy by joining fishing groups shows the higher effect on financial literacy. Additionally, savings and the geographical distance to nearby cities and bank branches emerge as determinants of financial literacy among Indonesian fishermen. Implications – This research enhances the existing literature by providing a nuanced understanding of the determinants of financial literacy in a specific maritime context. It offers valuable insight for policymakers, financial institutions, and community development organizations aiming to improve financial capabilities within fishing communities.